Commodification Of Papua Social Conflicts In Social Media In National Security Perspective - yusuf syibly ramadhan; maria puspitasari (MEDIALOG: Jurnal Ilmu Komunikasi, 2021)
Hoaxes are information manipulated for a specific purpose, in Papua in 2019 the spread of hoax information on the issue of racism was widespread on social media and triggered riots in various parts of Papua. This study uses a qualitative descriptive method, the data is processed through extracting, tracing books, newspapers, newspapers, magazines, journals, and social media observations and other notes that can support research to see how the phenomenon of the commodification of the Papuan conflict is then presented in the form of hoax information. as well as make descriptions, descriptions or paintings in a systematic, factual and accurate manner regarding the facts, characteristics and relationships between the phenomena being investigated. The results found that the commodification of the Papuan conflict, especially the issue of racism, was then packaged in the form of hoax information using hostility narratives or NKRI VS Papua which then caused a threat to national security